Optogenetic intervention of seizures improves spatial memory in a mouse model of chronic temporal lobe epilepsy - Hannah K. Kim; Tilo Gschwind; Theresa Nguyen; Anh Bui; Sylwia Felong; Kristen Ampig; David Y. Suh; Annie Vogel Ciernia; Marcelo A. Wood; Iván Soltész (2020)
Abstract Objective To determine if closed‐loop optogenetic seizure intervention, previously shown to reduce seizure duration in a well‐established mouse model chronic temporal lobe epilepsy (TLE), also improves the associated comorbidity of impaired spatial memory. Methods Mice with chronic, spontaneous seizures in the unilateral intrahippocampal kainic acid model of TLE, expressing channelrhodopsin in parvalbumin‐expressing interneurons, were implanted with optical fibers and electrodes, and tested for response to closed‐loop light intervention of seizures. Animals that responded to closed‐loop optogenetic curtailment of seizures were tested in the object location memory test and then given closed‐loop optogenetic intervention on all detected seizures for 2 weeks. Following this, they were tested with a second object location memory test, with different objects and contexts than used previously, to assess if seizure suppression can improve deficits in spatial memory. Results Animals that received closed‐loop optogenetic intervention performed significantly better in the second object location memory test compared to the first test. Epileptic controls with no intervention showed stable frequency and duration of seizures, as well as stable spatial memory deficits, for several months after the precipitating insult. Significance Many currently available treatments for epilepsy target seizures but not the associated comorbidities, therefore there is a need to investigate new potential therapies that may be able to improve both seizure burden and associated comorbidities of epilepsy. In this study, we showed that optogenetic intervention may be able to both shorten seizure duration and improve cognitive outcomes of spatial memory.